PENGARUH KOMPENSASI TERHADAP SEMANGAT KERJA PEGAWAI DINAS LINGKUNGAN HIDUP DAN KEHUTANAN KABUPATEN SUMEDANG - Rika Kusdinar; Dede Any Sumarny; Dian Agustian Trynanda; Herdian Wibawa; Rika Santika; Sintya Ratna Dewi (LPPM UNSAP & FISIP UNSAP, 2020)
The purpose of the research conducted by the researchers was to determine the effect of compensation on employee morale in the Sumedang district's environment and forestry service. The method used in this study is a quantitative research method, namely research based on the philosophy of positivism, this study uses data processes in the form of numbers as a tool for conducting research studies, so the results of research calculations in the form of numbers. The members obtained in this type of research determine the population and sample. The sampling technique used is the saturation sampling technique, with a population of 63 people. Based on the results of the research, the research can illustrate that the compensation provided by the Department of Environment and Forestry of Sumedang Regency has reached 80.90% and the figure is categorized Very Good, as well as the level of employee morale at the Department of Environment and Forestry of Sumedang Regency which reaches 83, 46% and the figure is categorized Very Good. The compensation relationship with the morale of the Office of Environment and Forestry of Sumedang Regency with a correlation coefficient of 0.539 is in the medium category. While the effect of compensation on the morale of employees of the Department of Environment and Forestry in Sumedang Regency reached 29.1%, the remaining 70.9% was influenced by other variables not examined by researchers.